Lung cells support osteosarcoma cell migration and survival. Issue 1 (December 2017) - Yu, Shibing; Fourman, Mitchell; Mahjoub, Adel; Mandell, Jonathan; Crasto, Jared; Greco, Nicholas; Weiss, Kurt
Abstract Background Osteosarcoma (OS) is the most common primary bone tumor, with a propensity to metastasize to the lungs. Five-year survival for metastatic OS is below 30%, and has not improved for several decades despite the introduction of multi-agent chemotherapy. Understanding OS cell migration to the lungs requires an evaluation of the lung microenvironment. Here we utilized an in vitro lung cell and OS cell co-culture model to explore the interactions between OS and lung cells, hypothesizing that lung cells would promote OS cell migration and survival. The impact of a novel anti-OS chemotherapy on OS migration and survival in the lung microenvironment was also examined. Methods Three human OS cell lines (SJSA-1, Saos-2, U-2) and two human lung cell lines (HULEC-5a, MRC-5) were cultured according to American Type Culture Collection recommendations. Human lung cell lines were cultured in growth medium for 72 h to create conditioned media. OS proliferation was evaluated in lung co-culture and conditioned media microenvironment, with a murine fibroblast cell line (NIH-3 T3) in fresh growth medium as controls. Migration and invasion were measured using a real-time cell analysis system. Real-time PCR was utilized to probe for Aldehyde Dehydrogenase (ALDH1) expression. Osteosarcoma cells were also transduced with a lentivirus encoding for GFP to permit morphologic analysis with fluorescence microscopy. The anti-OS efficacy of Disulfiram, an ALDH-inhibitor previously shown to inhibit OS cell proliferation and metastasis in vitro, was evaluated in each microenvironment. Results Lung-cell conditioned medium promoted osteosarcoma cell migration, with a significantly higher attractive effect on all three osteosarcoma cell lines compared to basic growth medium, 10% serum containing medium, and NIH-3 T3 conditioned medium (p <0.05). Lung cell conditioned medium induced cell morphologic changes, as demonstrated with GFP-labeled cells. OS cells cultured in lung cell conditioned medium had increased alkaline phosphatase staining. Conclusions Lung endothelial HULEC-5a cells are attractants for OS cell migration, proliferation, and survival. The SJSA-1 osteosarcoma cell line demonstrated greater metastatic potential than Saos-2 and U-2 cells. ALDH appears to be involved in the interaction between lung and OS cells, and ALP may be a valuable biomarker for monitoring functional OS changes during metastasis.